2015
DOI: 10.1111/jph.12451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sweet Potato Feathery Mottle Virus and Sweet Potato Chlorotic Stunt Virus on the Yield of SweetPotato in Uganda

Abstract: Sweet potato feathery mottle virus (SPFMV) and Sweet potato chlorotic stunt virus (SPCSV) are the most common viruses infecting sweetpotato in Uganda. Field plots planted with graft inoculated plants of virus-free cultivars Beauregard, Dimbuka, Ejumula, Kabode and NASPOT 1 were used to assess the effect of SPFMV and SPCSV on yield and quality of sweetpotatoes in two agro-ecologies. SPFMV spreads rapidly to control plots at Makerere University Agricultural Research Institute Kabanyolo (MUARIK), and these plots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 24 publications
6
31
1
1
Order By: Relevance
“…This is in agreement with the earlier observations by Wasswa (2010), Adikini et al (2016) and Gibson et al (2014) though most of these authors did not vary temperatures to wide ranges. Sweet potato infected with SPVD and grown under glasshouse conditions produce little or no tuber yield, and this observation concurs with that of Adikini et al (2016). SPVD presence also influenced the number of leaves.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in agreement with the earlier observations by Wasswa (2010), Adikini et al (2016) and Gibson et al (2014) though most of these authors did not vary temperatures to wide ranges. Sweet potato infected with SPVD and grown under glasshouse conditions produce little or no tuber yield, and this observation concurs with that of Adikini et al (2016). SPVD presence also influenced the number of leaves.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported that some areas such as central Uganda had higher SPVD incidences and severities than for instance the eastern region (Adikini et al, 2016). The two regions differ in average ambient temperature, among other climatic aspects; with the eastern being hotter than the central region.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations